TRANSFORMING THE NARRATIVE ELEMENTS FROM THE FITZGERALD INTO FINCHER’S THE CURIOUS CASE OF BENJAMIN BUTTON - Saksono, Suryo Tri; Rahmawati, Ana (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2014)
Adaptation is the process of transforming one form of art into another one. Many decent films are adapted from great literary work. In the adaptation process, some changes occur in film. It is because film is produced in different way from novel. This study focuses on the transformation of the narrative elements from the short story into the film entitled The Curious Case of Benjamin Button. This study uses the theory of adaptation by Linda Seger to explain the adaptation process from the short story into the film as the sources of data. There are three processes of adaptation: condensing and expanding the material, the process of making the film commercial, and varied changing. The narrative elements theory is also used to explain the structure that builds the literary work.